2021
DOI: 10.1371/journal.pone.0253297
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Evaluation of charged membrane filters and buffers for concentration and recovery of infectious salmon anaemia virus in seawater

Abstract: Infectious salmon anaemia virus (ISAV) is the cause of an important waterborne disease of farmed Atlantic salmon. Detection of virus in water samples may constitute an alternative method to sacrificing fish for surveillance of fish populations for the presence of ISA-virus. We aimed to evaluate different membrane filters and buffers for concentration and recovery of ISAV in seawater, prior to molecular detection. One litre each of artificial and natural seawater was spiked with ISAV, followed by concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
(65 reference statements)
2
5
0
Order By: Relevance
“…ISAV prevalence in seawater tanks and in the gill and heart samples at the peak of infection followed the same progression. In our previous laboratory experiments, limit of detection (LOD) of virus for the concentration method A was calculated to be 1.1 × 10 4 ISAV RNA copies/L of natural seawater [ 20 ], which is similar to the average virus detection found in the present study. Nevertheless, in field condition, reliable detection of ISAV, which may be present in the seawater at very low concentrations, may require some further optimization of the method.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…ISAV prevalence in seawater tanks and in the gill and heart samples at the peak of infection followed the same progression. In our previous laboratory experiments, limit of detection (LOD) of virus for the concentration method A was calculated to be 1.1 × 10 4 ISAV RNA copies/L of natural seawater [ 20 ], which is similar to the average virus detection found in the present study. Nevertheless, in field condition, reliable detection of ISAV, which may be present in the seawater at very low concentrations, may require some further optimization of the method.…”
Section: Discussionsupporting
confidence: 85%
“…A comparison of the performance of the five different concentration methods showed that the use of the method of applying the electronegatively charged filter together with NucliSENS ® lysis buffer for elution resulted in detection of significantly higher levels of ISAV RNA from seawater by RT-ddPCR compared to the other four methods. The higher ISAV RNA concentration detected from seawater with the MF - /buffer 1 method (A) correlates with results from an in vitro study carried out with seawater samples spiked with ISAV [ 20 ], as well as from recent equivalent studies with salmonid alphavirus in seawater [ 20 , 26 ].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations